Design and modeling of induction motor using opera 2D based on aluminum material - Ismail, Daut, Prof. Dr.; Anayet, Karim; Tirapathy, S. (Institute of Electrical and Electronics of Engineering (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/